A novel tigecycline resistance gene, tet(X6), on an SXT/R391 integrative and conjugative element in a Proteus genomospecies 6 isolate of retail meat origin. (4th February 2020) - He, Dandan; Wang, Liangliang; Zhao, Shiyu; Liu, Lanping; Liu, Jianhua; Hu, Gongzheng; Pan, Yushan
Abstract: Objectives: To characterize a novel tigecycline resistance gene, tet (X6), and a novel SXT-related integrative and conjugative element (ICE), ICE Pgs6Chn1, found in a tigecycline-resistant Proteus genomospecies 6 strain, T60. Methods: Strain T60 was identified by the VITEK 2 system, biochemical reactions and an SNP-based approach. The genetic profile of strain T60 was determined by WGS analysis. ICE Pgs6Chn1 was analysed by PCR, conjugation experiments and bioinformatics tools. tet (X6) was characterized by cloning and protein structure prediction. Results: Strain T60 was resistant to ampicillin, tetracycline, tigecycline, florfenicol, colistin and kanamycin, but susceptible to cefotaxime; it also exhibited high MICs of eravacycline (32 mg/L) and omadacycline (>64 mg/L). Only one chromosome was identified and tet (X6) was located in chromosomal ICE Pgs6Chn1, a member of the SXT/R391 ICE family, of 114 368 bp and encoding the antimicrobial resistance genes floR, strB, strA, aph(3′)-Ia, aac(3)-IV, aph(4)-Ia, tet (X6) and sul2 . The circular intermediate of ICE Pgs6Chn1 was detected by PCR and sequencing, but conjugation experiments showed that it was not self-transmissible. Cloning of the novel gene tet (X6) and protein structure prediction revealed that Tet(X6) confers tigecycline resistance. Conclusions: To our knowledge, this is the first report of a novel SXT/R391 ICE in a Proteus genomospecies 6 strain. Importantly, a novel high-level tigecycline resistance gene, tet (X6), emerged for the first time in the SXT/R391 element of Proteus genomospecies 6, revealing that ICEs may serve as an important platform for the accumulation of antibiotic resistance genes.